2020
DOI: 10.1016/j.euo.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Complications in Postchemotherapy Retroperitoneal Lymph Node Dissection for Nonseminoma Germ Cell Tumour: A Population-based Study from the Swedish Norwegian Testicular Cancer Group

Abstract: Background Reports on perioperative complications after Post-Chemotherapy Retroperitoneal lymph node dissection (PC-RPLND) for Non-Seminoma Germ Cell Tumour (NSGCT) are from experienced single centres, with a lack of population-based studies. Objective To assess the complications of bilateral and unilateral PC-RPLND. Design, Setting, Participants Prospective, population-based observational multicentre study that included all patients with NSGCT that underwent PC-RPLND in Norway and Sweden 2007 to 2014. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 16 publications
(41 reference statements)
4
28
1
Order By: Relevance
“…small bowel obstruction and postoperative ileus. In accordance with our finding, a Scandinavian study reported a higher rate of adjunctive measures in left-sided resections [38].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…small bowel obstruction and postoperative ileus. In accordance with our finding, a Scandinavian study reported a higher rate of adjunctive measures in left-sided resections [38].…”
Section: Discussionsupporting
confidence: 93%
“…No perioperative mortality was observed in our series, which is consistent with other recent reports [8,13,27,30,31,33,34,36]. Low mortality rates of 0.20 to 1.6% [12,29,32,35,38,39] were reported in some other studies ( Table 5). In a Dutch series, one death due to anaesthesiological problems was reported [40].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The only major complication in our series was a lymphocele requiring drainage. This is in contrast with several population-based studies on open RPLND, which have reported average complication rates of ~ 25% [30,31].…”
Section: Discussioncontrasting
confidence: 83%